2020
DOI: 10.2174/2212798411666200316153148
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess Optimization for Exopolysaccharides Production by Ganoderma lucidum in Semi-industrial Scale

Abstract: Background: For many years, ganoderma was highly considered as biofactory for the production of different types of bioactive metabolites. Of these bioactive compounds, polysaccharides gained many attentions based on their high biotherapeutic properties. Therefore, special attention have been paid during the last years for production of mushrooms bioactive compounds in closed cultivation system to shorten the cultivation time and increase the product yield. Results and Discussion: Therefore, this work is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, this study revealed that a controlled pH strategy improved EPS production and pleuran production with values of 1.98 g/L and 0.4 g/g to be achieved [43]. A higher EPS production compared to our study was achieved only for a Ganoderma lucidum EPS that was produced in a 16 L stirred tank bioreactor, with a production value of 5.0 g/L after fermentation in controlled pH conditions [44]. These two studies suggest that future fermentation of P. ostreatus using red light with a controlled pH strategy process could further increase EPS production.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, this study revealed that a controlled pH strategy improved EPS production and pleuran production with values of 1.98 g/L and 0.4 g/g to be achieved [43]. A higher EPS production compared to our study was achieved only for a Ganoderma lucidum EPS that was produced in a 16 L stirred tank bioreactor, with a production value of 5.0 g/L after fermentation in controlled pH conditions [44]. These two studies suggest that future fermentation of P. ostreatus using red light with a controlled pH strategy process could further increase EPS production.…”
Section: Discussionmentioning
confidence: 52%
“…The recovering process used 6000 rpm centrifugation for 10 minutes at 4C. This study required special extra supernatant utilization to estimate SA by using (HPLC) Waters 2690 Alliance Separations Module with a flow rate of (0.6) m/min, UV detection of (210) nm, Mobile Phase H 2 SO 4 of (0.005N), Waters 996 Photodiode Array Detector and Column: Hi-Plex H, 300  7.7 mm with guard column and temperature at 40C (Alsaheb et al, 2020).…”
Section: Succinic Acid Determinationmentioning
confidence: 99%
“…Presumably, the sugar diminishes has occurred approximately between 36 h to 48 h. The quantity of dissolved oxygen (DO) decreased gradually from 100% to 25.00% at the end of fermentation. All the findings at the bioreactor stage could be explained by the effects of corn fiber (sugar complexity) and the production of many acids during the Actinobacillus succinogenes fermentation pathway (Alsaheb et al, 2020;Raje Nimbalkar et al, 2022).…”
Section: Succinic Acid Production and Kinetics Of Bioprocess Paramete...mentioning
confidence: 99%
“…In addition, these macromolecules are relatively non-toxic to normal cells and tissues, which affords no significant side effects if used as therapeutic drugs [3]. Based on such evidence, many studies about fungal polysaccharides, their sources, and how to produce them have been published, showing the potential of biotechnological Molecules 2023, 28, 4356 2 of 16 tools to obtain bioactive compounds [1][2][3][4][5]. Among the biological properties described for such macromolecules, it can be mentioned: antioxidant, anti-inflammatory, antiangiogenic, antiviral, antitumor, and immunomodulatory activities [6][7][8].…”
Section: Introductionmentioning
confidence: 99%